The Oxford guide to the Book of common prayer a worldwide survey - Hefling, Charles C.; Shattuck, Cynthia L., 1947- (Oxford ; New York : Oxford University Press, 2006)
The Book of Common Prayer runs like a golden thread through the history of the Church of England and the worldwide Anglican Communion. The Oxford Guide to the Book of Common Prayer is the first comprehensive guide to the history and usage of the original Book of Common Prayer and its numerous descendants throughout the world. It shows how a seminal text for Christian worship and devotion has inspired a varied family of religious resources that have had an influence far beyond their use in the churches of a single tradition. The Guide is unique. In it, experts from every part of the globe and e
Introduction : Anglicans and common prayer / Charles Hefling -- 'But one use' : the birth of the classical prayer book. Worship by the book / Kenneth Stevenson. Cranmer and common prayer / Gordon Jeanes. The prayer book 'noted' / Robin A. Leaver. From Elizabeth I to Charles II / Bryan Spinks. Early translations / J. Robert Wright. The 'liturgy of comprehension' / Charles Hefling. The shape of the classical Book of common prayer / J. Neil Alexander. The state services / Charles Hefling -- The social and cultural life of the prayer book. The prayer book and the parish church : from the Elizabethan settlement to the Restoration / Judith Maltby. The prayer book and the parish church : from the Restoration to the Oxford movement / Jeremy Gregory. Prayer book architecture / James F. White. Prayer books and printers / Martin W. Hutner. The prayer book as 'sacred text' / Kenneth Stevenson. The prayer book as literature / Paul G. Stanwood -- The prayer book outside England. Plantations, missions, and colonies / William L. Sachs. The prayer book in Anglican churches. (Scotland : Episcopalians and nonjurors / Charles Hefling. The colonies and states of America / Marion J. Hatchett. British North America and Canada / William R. Blott. Southern Africa / Cynthia Botha. Ireland / Brian Mayne). The prayer book and other traditions. (John Wesley and the Methodists / Karen B. Westerfield Tucker. King's Chapel and the Unitarians / Carl Scovel. Churches in the continuing Anglican tradition / Lesley A. Northup. The prayer book and Lutheranism / Philip H. Pfatteicher) -- From uniformity to family resemblance : prayer books in the twentieth century. The winds of change / Colin Buchanan. The prayer book 'crisis' in England / Bryan Spinks. The legacy of the Church of South India / Colin Buchanan. The liturgical movement and its consequences / John F. Baldovin. Preserving the classical prayer books / Colin Buchanan -- Family portraits : prayer books today. Inculturation and Anglican worship / Ian T. Douglas. Rites and books in Africa. (Anglican liturgies in Eastern Africa / Esther Mombo. The Anglican church of Kenya / Grant LeMarquand. The Church of Nigeria : the Book of common prayer / David C. Okeke. The Church of Nigeria : Occasional services / Emmanuel Ekpunobi. Central African prayer books / Titus Presler. The Province of Southern Africa / Michael Nuttall. Other African provinces : Burundi, Rwanda, and Congo). Rites and books in the Pacific. (The Anglican church of Australia / Charles Sherlock. The Anglican church in Aotearoa, New Zealand, and Polynesia / Kenneth Booth. From Te rawiri to the New Zealand prayer book / Jenny Te Paa. The church of Melanesia / Terry Brown. The Anglican Church of Papua New Guinea / Justus VanHouten. Hawaii). Rites and books in the Americas. (The Episcopal Church in the U.S.A. / Lesley A. Northup. Native American translations. The Anglican Church of Canada / John W.B. Hill. Indigenous Canadian translations. The province of the West Indies / Charles Hefling. The book of common prayer in Spanish / Juan M.C. Oliver). Rites and books in Asia. (The Episcopal Church in the Philippines / Tomas S. Maddela. Japan : Nippon Sei Ko Kai / John M. Yoshida. The Chinese prayer book / Sze-Kar Wan. The Anglican Church of Korea / Nak-Hyon Joseph Joo. The province of Myanmar (Burma) / Katherine E. Babson. The Episcopal Church in Jerusalem and the Middle East). Rites and books in Europe. (The Church of England : Common worship / Trevor Lloyd. The Scottish Episcopal Church / Gianfranco Tellini. The church in Wales / Robert Paterson. The Church of Ireland / Harold Miller. Anglican churches in Europe / Jeffery Rowthorn) -- Worship in the prayer book family. Anglicans and liturgical revision / Richard Geoffrey Leggett. The daily office / John Gibaut. The Eucharist / Ronald Dowling. Sanctifying time : the calendar / Leonel L. Mitchell. Rites of initiation / Ruth A. Meyers. Catechisms / James F. Turrell. Marriage / Gillian Varcoe. Funeral rites / Trevor Lloyd. Anglican ordinals / Richard Geoffrey Leggett -- The future of the Book of common prayer. The Book of common prayer and technology / Donald Kraus. The prayer book in cyberspace / Clayton L. Morris. The future of common prayer / Pierre W. Whalon.
Map on lining papers.
Includes bibliographical references (p. [581]-595) and index.
Description based on print version record.
Keywords: Anglican Communion -- Liturgy -- Texts -- History; Church of England. -- History; Episcopal Church. -- History; Anglican Communion; RELIGION -- Institutions & Organizations; RELIGION -- Christian Rituals & Practice -- Worship & Liturgy; Electronic books